Determination of Cetuximab in Plasma by Liquid Chromatography–High-Resolution Mass Spectrometry Orbitrap With a Stable Labeled 13C, 15N-Cetuximab Internal Standard. Issue 4 (August 2019) - Millet, Aurélien; Lebert, Dorothée; Picard, Guillaume; You, Benoit; Ceruse, Philippe; Guitton, Jérôme
Abstract : Background: Cetuximab (CTX) is a chimeric IgG1 Kappa monoclonal antibody used to treat head and neck cancer and colorectal cancer. Previous clinical studies indicated that the pharmacokinetics of CTX influences patient survival. Thus, individualizing CTX treatment by measuring trough levels of the drug in plasma could have a major impact on clinical efficacy. Methods: To measure these levels, a full-length stable isotope-labeled CTX standard was used in a generic, rapid, and high-throughput sample preparation protocol based on IgG capture followed by trypsin digestion, on-line solid-phase extraction cleanup, and liquid chromatography–high resolution mass spectrometry (LC-HRMS). Results: The optimized method displayed good analytical performance and was linear over a range from 5 to 150 mcg/mL. The within-run and between-run imprecision of the assay were equal to or less than 10%, for 6 replicates at 3 different concentrations and for runs performed on 5 separate days. The plasma CTX concentrations in 19 patients were also determined. Conclusions: The results showed that quantification of mAb in clinical samples does not strictly require a tandem mass spectrometry system, and LC-HRMS is also relevant in this context. This first study implementing a quantitative LC-HRMS assay with a specific stable isotope-labeled mAb internal standard paves the way for more robust clinical monitoring of anticancer mAbs. Abstract : Supplemental Digital Content is Available in the Text.